Предмет: Алгебра,
автор: Аноним
Помогите пожалуста
x^3+3x^2-6x-8=0
Ответы
Автор ответа:
0
разделим на (x-1), затем разделим на (х-2), получим
Отсюда видно
Отсюда видно
Приложения:
Автор ответа:
0
x^3 + 3x^2 + 6x + 8 = 0
(x^3 + 8) + (3x^2 + 6x) = 0
(x+2)(x^2 -2x+2^2) + 3x*(x+2) = 0
(x+2) * [x^2 - 2x + 4 + 3x) = 0
(x+2) * (x^2 + x + 4) = 0
1) x+2 = 0 => x = -2
2) x^2 + x + 4 = 0
D<0 => действительных корней нет
Ответ: х = -2
(x^3 + 8) + (3x^2 + 6x) = 0
(x+2)(x^2 -2x+2^2) + 3x*(x+2) = 0
(x+2) * [x^2 - 2x + 4 + 3x) = 0
(x+2) * (x^2 + x + 4) = 0
1) x+2 = 0 => x = -2
2) x^2 + x + 4 = 0
D<0 => действительных корней нет
Ответ: х = -2
Автор ответа:
0
Подожди, так в условии другие знаки
Автор ответа:
0
x^3+3x^2-6x-8=0 а не x^3+3x^2+6x+8=0
Похожие вопросы